Analisis Faktor Kecemasan Ibu Dalam Pendampingan Anak Belajar Di Rumah - Shanti Rosmaharani; Dian Anisia Widyaningrum (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: This study aims to determine the factors that influence maternal anxiety in assisting children to study at home / study from home. Methods: The design of this study used a correlational analytic design with a